Synthesis and Performance for Hydrogen Production of Carbon Nanotubes-ZnTHPP-TiO2 Nanocomposite Catalyst - Wang, Xue-Jing; Zhu, Fangkun; Hu, Linfeng (Asian Journal of Chemistry, 2012)
Using carbon nanotubes (CNTs) as temperate, CNTs-ZnTHPP-TiO2 nanocomposite was prepared by sol-gel method. Its structure was characterized by XRD, TEM and EDS. The UV absorbing property was detected by the UV spectrophotometer. The results showed that nanocomposite was composed of carbon nanotube coated evenly by ZnTHPP-TiO2 particles, with diameter of 50-60 nm. ZnTHPP increases the visible light absorbable range of TiO2 significantly. As photocatalyst, CNTs-ZnTHPP-TiO2 nanocomposite has better performance for hydrogen production under irradiation of visible light and the rate of hydrogen production is the highest when the content of carbon nanotube is 40 %.